Noether’s theorem in statistical mechanics - Sophie Hermann (Nature Portfolio, 2021)
Noether’s Theorem relates symmetries to fundamental physical laws. Rather than applying the concept to an action integral in order to obtain conservation laws, here the authors consider Statistical Mechanical objects, such as the free energy and density and power functionals to derive exact force and torque sum rules.